Megaplasmid pRme2011a of Sinorhizobium meliloti Is Not Required for Viability - Oresnik, Ivan J. (American Society for Microbiology, 2000)
We report the curing of the 1,360-kb megaplasmid pRme2011a from Sinorhizobium meliloti strain Rm2011. With a positive selection strategy that utilized Tn5B12-S containing the sacB gene, we were able to cure this replicon by successive rounds of selecting for deletion formation in vivo. Subsequent Southern blot, Eckhardt gel, and pulsed-field gel electrophoresis analyses were consistent with the hypothesis that the resultant strain was indeed missing pRme2011a. The cured derivative grew as well as the wild-type strain in both complex and defined media but was unable to use a number of substrates as a sole source of carbon on defined media.